Uncommon complication: maggot infestation around tracheostomy tube wound - Singh, Jaswant; Soni, Anuj Kumar (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2025)
“GOD’S punishment for sinners” this is the name given to Myiasis (Maggots) in Hindu mythology, symbolizing divine retribution. Myiasis is caused by the larvae of dipterous flies, which feed on living or necrotic tissue of both humans and animals. It can affect various body sites, including the skin, eyes, ears, stomach, intestinal tract, and genitourinary areas. The condition primarily involves body cavities such as the nasal cavity, ears, non-healing ulcers, exophytic malignant growths, and cutaneous tissue. While myiasis around a tracheostomy tube is rare, it presents significant challenges in diagnosis and treatment. Here, we present the case of a 62-year-old male who developed myiasis around his tracheostomy tube. Physical examination revealed severe necrosis around the tracheostomy site, with multiple live maggots present in the affected tissue. After the removal of the tracheostomy tube, the patient was able to breathe without difficulty in a room air environment. A total of 30–40 live maggots were carefully extracted using tooth forceps and curved artery forceps. Surgical debridement and removal of necrotic tissue were performed to prevent further spread of infection and promote healing. This case underscores the importance of considering myiasis as a rare but potentially serious complication in patients with tracheostomies, highlighting the need for prompt intervention to prevent systemic infection.